Acute phase proteins in psoriasis - Biljan, Darko (Array, 2009)
Abstract: Psoriasis is a chronic, relapsing, inflammatory and hyperproliferative skin disorder. The levels of acute phase proteins are suggested to be elevated in those patients with acute disease. The expression of selected acute phase proteins as the parameters of humoral immunity has been analyzed in 70 patients with acute psoriasis and 40 healthy controls. The aim was to evaluate the inflammatory response in the exacerbation of psoriasis and to determine the correlation of these objective inflammatory parameters with clinical features of disease activity. Main demographic and epidemiologic features were, as well, analysed. The plasma levels of C-reactive protein (CRP) (c2 = 23.61; p<0.005), and alpha1-acid glycoprotein (a1-AGP) (c2 = 7.,42; p<0.01) were significantly increased in those patients with acute phase of the disease compared to healthy controls. Our results suggest that psoriasis is an inflammatory disease and therefore its worsening seemed to be linked to the increase in the inflammatory response. It seems that CRP and al-AGP levels could serve as important prognostic factors for the worsening of psoriasis